Creutzfeldt–Jakob disease with unusual presentation of peripheral neuropathy and ophthalmoplegia - Arwani, Mais (Avicenna J Med, 2018)
Creutzfeldt–Jakob disease (CJD) is a well-described disease. It is characterized by rapidly progressive dementia, myoclonus, ataxia, pyramidal, and extrapyramidal signs. There are well-defined electroencephalogram and magnetic resonance imaging (MRI) findings, and markers found in the cerebrospinal fluid (CSF). The gold standard for diagnosing CJD remains brain biopsy. We present a case of a patient with a family history of biopsy-proven CJD who initially presented with symptoms of peripheral neuropathy. A month later, he developed ataxia, ophthalmoparesis, and then dysarthria. His initial workup was relatively unrevealing, showing an elevated protein in his CSF. He was thought to have Miller Fisher syndrome variant of Guillain–Barré syndrome. He neither, however, responded to plasmapheresis nor IVIG. He later started to develop progressive dementia. Repeated MRI showed restricted diffusion in the caudate and putamen, as well as in the cortex (cortical ribboning). Lumbar puncture was then found to be positive for 14-3-3 protein, total-tau protein, and real-time quaking-induced conversion assay, which are highly suggestive of CJD. We present a case of CJD with an unusual presentation resulting in misdiagnosis, prolonged workup, and potentially harmful treatment modalities. This case highlights the importance of broadening our definition of CJD to encompass more cases with unusual presentations.